(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2024)
Background: Women with polycystic ovary syndrome (PCOS) have hyperandrogenemia and insulin resistance, which predispose them to prothrombotic conditions. D-dimer is a global marker of hemostatic dysfunction that has a contentious relationship with PCOS. Objective: To assess the association of D-dimer with PCOS and its manifestations. Methods: This case-control study enrolled 44 women with PCOS based on the International Evidence-based Guideline, 2018, and an equal number of matched healthy controls by convenient sampling. After obtaining informed consent, participants’ clinical data was taken, and fasting blood was drawn to measure glucose, lipid profile, hormones, and D-dimer. D-dimer was analyzed by latex immunofluorescence assay. Results: The D-dimer levels (mg/L) and status were statistically similar between the study groups [PCOS vs. control: 0.11 (0.10-0.17) vs. 0.13 (0.10-0.22), median (IQR), p= 0.673]. D-dimer levels did not vary according to the different characteristics of women with PCOS (p>0.05). D-dimer levels had no significant correlations with various clinical and biochemical characteristics among women with PCOS (p>0.05). Conclusion: This study found that D-dimer has no significant association with PCOS or its manifestations. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2024;3(2): 53-57